2015
DOI: 10.1002/2014jf003365
|View full text |Cite
|
Sign up to set email alerts
|

Complexity in salt marsh circulation for a semienclosed basin

Abstract: The fine details of overmarsh circulation remain largely unexplored and yet they are typically assumed to control many attributes of salt marsh material cycling, transport, and accretion. We characterized the spatial and temporal variability in overmarsh circulation at a 2 km2 Georgia, USA, salt marsh using field observations, dye tracer, and numerical simulations. The marsh bathymetry was created with a high‐precision Global Positioning System survey that details the geomorphic structure of intertidal creeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Another important aspect to consider is the Manning's roughness coefficient (n) associated with land cover classes in the model domain. We use updated emergent herbaceous wetland regions to assign n-coefficient values of subtidal channels (n = 0.017) and salt marsh platforms (n = 0.10) of Savannah similar to those reported in Sullivan et al (2015). The remaining n-coefficient values of the 2016 NLCD are initially derived from Liu et al (2018) and further calibrated as described in the next section.…”
Section: Wetland Elevation Correctionmentioning
confidence: 99%
“…Another important aspect to consider is the Manning's roughness coefficient (n) associated with land cover classes in the model domain. We use updated emergent herbaceous wetland regions to assign n-coefficient values of subtidal channels (n = 0.017) and salt marsh platforms (n = 0.10) of Savannah similar to those reported in Sullivan et al (2015). The remaining n-coefficient values of the 2016 NLCD are initially derived from Liu et al (2018) and further calibrated as described in the next section.…”
Section: Wetland Elevation Correctionmentioning
confidence: 99%
“…(1) and t is the length of time that a particle of water stays in the system, and a and b are dispersion coefficients that influence the time variation of the random spreading process and emerge from model calibration (Bent et al, 1991). For these 2-D flow simulations, a roughness length parameter of 0.001 m was specified (Nepf & Ghisalberti, 2008;Raupach, 1994;Sullivan et al, 2015), and this in turn helped determine the logarithmic vertical velocity profile.…”
Section: Model Description and Setupmentioning
confidence: 99%
“…In other words, Blanton et al () implied that first‐order creek systems facilitate greater overall salt marsh circulation. Later, the same site was surveyed in high detail using a real‐time kinematic global positioning system, and Sullivan et al () used the resulting DEM in simulations of overmarsh flow. They showed highly complex flow patterns in both space and time, and they associated this response with the submergence/emergence of decimeter‐scale topography.…”
Section: Introductionmentioning
confidence: 99%
“…; Sullivan et al. ). However, it is extremely time consuming to simulate a real‐world salt marsh system with such a small grid size and a small time step.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review of Manning coefficients revealed a large range of values between 0.006 and 0.63 s m −1/3 (Sullivan et al. ). Such a wide range of bottom roughness values makes it difficult to calibrate models.…”
Section: Introductionmentioning
confidence: 99%